Transmission of Local Islamic Texts in Islamic Education: Materials, Actors, and the Historical Trajectory of Islamic Knowledge in Borneo - Erwin Mahrus; Zaenuddin Hudi Prasojo; Sukino Sukino; Nopi Purwanti; Bayu Suratman (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study investigates the transmission of local Islamic texts used in West Kalimantan (Borneo, Indonesia) for Islamic religious education during the 20th century. It addresses a research gap concerning how Islamic knowledge was disseminated through printed works by local scholars. The research adopts a qualitative historical approach, employing content analysis through comprehensive reading, categorization, interpretation, and synthesis of primary sources. The findings reveal that Islamic educational materials in Borneo encompassed texts on theology (‘aqīdah, usūl al-dīn), jurisprudence (fiqh), history, and Qur’anic studies (‘ulūm al-Qur’ān), distributed via both commercial transactions and gifts by peers, religious officials, and sales agents. The study concludes that these transmission networks extended to neighboring Islamic sultanates and even reached Brunei Darussalam. Furthermore, these networks significantly influenced the development of educational institutions that integrated Islamic religious sciences with Western knowledge. The epistemology of Islamic education in Kalimantan was not merely a preserved tradition but a modern system open to knowledge, enabling the transmission of Islamic knowledge beyond formal institutions into broader society. This research makes an essential contribution to the development of Islamic education and the mapping of Islamic scholarship networks in the archipelago.